Myocardial strain in healthy adults across a broad age range as revealed by cardiac magnetic resonance imaging at 1.5 and 3.0T: Associations of myocardial strain with myocardial region, age, and sex. Issue 5 (22nd April 2016) - Mangion, Kenneth; Clerfond, Guillaume; McComb, Christie; Carrick, David; Rauhalammi, Samuli M.; McClure, John; Corcoran, David S.; Woodward, Rosemary; Orchard, Vanessa; Radjenovic, Aleksandra; Zhong, Xiaodong; Berry, Colin
Abstract : Purpose: To assess myocardial strain using cine displacement encoding with stimulated echoes (DENSE) using 1.5T and 3.0T MRI in healthy adults. Materials and Methods: Healthy adults without any history of cardiovascular disease underwent magnetic resonance imaging (MRI) at 1.5T and 3.0T within 2 days. The MRI protocol included balanced steady‐state free‐precession (b‐SSFP), 2D cine‐echo planar imaging (EPI)‐DENSE, and late gadolinium enhancement in subjects >45 years. Acquisitions were divided into six segments; global and segmental peak longitudinal and circumferential strain were derived and analyzed by field strength, age, and gender. Results: In all, 89 volunteers (mean age 44.8 ± 18.0 years, range: 18–87 years) underwent MRI at 1.5T, and 88 of these subjects underwent MRI at 3.0T (1.4 ± 1.4 days between the scans). Compared with 3.0T, the magnitudes of global circumferential (–19.5 ± 2.6% vs. –18.47 ± 2.6%; P = 0.001) and longitudinal (–12.47 ± 3.2% vs. –10.53 ± 3.1%; P = 0.004) strain were greater at 1.5T. At 1.5T, longitudinal strain was greater in females than in males: –10.17 ± 3.4% vs. –13.67 ± 2.4%; P = 0.001. Similar observations occurred for circumferential strain at 1.5T (–18.72 ± 2.2% vs. –20.10 ± 2.7%; P = 0.014) and at 3.0T (–17.92 ± 1.8% vs. –19.1 ± 3.1%; P = 0.047). At 1.5T, longitudinal and circumferential strain were not associated with age after accounting for sex (longitudinal strain P = 0.178, circumferential strain P = 0.733). At 3.0T, longitudinal and circumferential strain were associated with age ( P < 0.05). Longitudinal strain values were greater in the apico‐septal, basal‐lateral, and mid‐lateral segments and circumferential strain in the inferior, infero‐lateral, and antero‐lateral LV segments. Conclusion: Myocardial strain parameters as revealed by cine‐DENSE at different MRI field strengths were associated with myocardial region, age, and sex. J. Magn. Reson. Imaging 2016;44:1197–1205.